PENGARUH KERAGAMAN PRODUK DAN KEPERCAYAAN KONSUMEN DALAM MENENTUKAN MINAT BELI KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO SEJAHTERA DI MANGARAN - Andrianas, Yoga; Tulhusnah, Lusiana; Praja, Yudha (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
The business world that is growing rapidly is both a challenge and a threat for business actors in order to calm the competition and maintain the viability of the company. The marketing concept is all company activities in marketing planning as an effort to achieve company goals. The marketing concept is a concept with a point of marketing is a concept with an emphasis on consumer needs, focusing more on feeling and responding to what consumers need. Especially for customers or consumers at the prosperous store by increasing the consumers at the Mangaran Prosperous shop, Situbondo Regency. The purpose of this study was to analyze and examine the effect of product diversity and consumer trust in determining consumer buying interest on purchasing decisions at the Prosperous Stores in Mangaran. The population in this study are consumers at Toko Sejahtera in Mangaran, Situbondo Regency. The sampling method is determined by probability sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model – Partial Least Square (PLS-SEM). The results of hypothesis testing the direct effect of using the Smart PLS 3.0 application, product diversity has a significant positive effect on consumer buying interest, consumer trust has a significant positive effect on consumer buying interest, product diversity has a significant positive effect on purchasing decisions, consumer trust has a significant positive effect on purchasing decisions, Consumer buying interest has a significant positive effect on purchasing decisions, product diversity on purchasing decisions through consumer buying interests has a significant positive effect, consumer confidence in purchasing decisions through consumer buying interests has a significant positive effect.